THE URGENCY OF USE OF E-REPORT FOR EDUCATION REPORTING OF STUDENTS WITH SPECIAL NEEDS IN THE SOCIETY 5.0 ERA - Rahma, Lailatul; Ulfatin, Nurul; Sunarni, Sunarni (Jurnal Visi Ilmu Pendidikan, 2025)
The issue of inclusive education in Indonesia still has many problems, which can be seen through the APS for children with special needs in the Society 5.0 Era. One of the causes is the inability of education to analyze and optimize the potential of students with special needs. This research uses a qualitative approach with data collection methods in the form of interviews, documentation, and observation. The E-Report design initiated by researchers based on the findings of researchers at the SLB Autis Laboratorium UM is expected to be able to accommodate the problems and needs of educational service customers. Apart from that, the available features also try to provide an overview of the students' condition through pictures, photos, videos, recordings, and graphics, which try to minimize the sensitivity of parents of students who have children with special needs.